A complete Neandertal mitochondrial genome sequence determined by high-throughput sequencing - Green, Richard E. (2008)
A complete mitochondrial (mt) genome sequence was reconstructed from a 38,000-year-old Neandertal individual using 8,341 mtDNA sequences identified among 4.8 Gb of DNA generated from ~0.3 grams of bone. Analysis of the assembled sequence unequivocally establishes that the Neandertal mtDNA falls outside the variation of extant human mtDNAs and allows an estimate of the divergence date between the two mtDNA lineages of 660,000±140,000 years. Of the 13 proteins encoded in the mtDNA, subunit 2 of cytochrome c oxidase of the mitochondrial electron transport chain has experienced the largest number of amino acid substitutions in human ancestors since the separation from Neandertals. There is evidence that purifying selection in the Neandertal mtDNA was reduced compared to other primate lineages suggesting that the effective population size of Neandertals was small.